Reshaping the Society Face through The Culture of Horror Told in Shirley Jackson’s The Lottery - Sari, Fani Alfionita; Tur, Ajar Pradika Ananta (Universitas Ahmad Dahlan, 2019)
Building a new society can be implemented through cutting the chain of a certain generation. Then, brainwash to younger one will be the powerful weapon to change the face of the society by the authority. This study analyzes the use of perlocutionary acts used by characters in Sirley Jackson's short story, The Lottery, that tells the redaers about the culture of horror expressed by the characters to reshape the face of the society. The descriptive qualitative method was used to investigate the essence of the culture of horror through perlocutionary acts. Besides, the contextual method was also applied to support the meaning of the culture of horror in the form of narration in the short story. The result of this study is that the perlocutionary acts used have 4 out of 5 parts according to the speaker's expression, namely: a) convincing, b) inviting, c) blocking, d) surprising. Then the effects of this perlocutionary act can create a horror effect based on the context, culture, and background of the story.Building a new society can be implemented through cutting the chain of a certaingeneration. Then, brainwash to younger one will be the powerful weapon to changethe face of the society by the authority. This study analyzes the use of perlocutionaryacts used by characters in Sirley Jackson's short story, The Lottery, that tells theredaers about the culture of horror expressed by the characters to reshape the faceof the society. The descriptive qualitative method was used to investigate the essenceof the culture of horror through perlocutionary acts. Besides, the contextual methodwas also applied to support the meaning of the culture of horror in the form ofnarration in the short story. The result of this study is that the perlocutionary actsused have 4 out of 5 parts according to the speaker's expression, namely: a)convincing, b) inviting, c) blocking, d) surprising. Then the effects of thisperlocutionary act can create a horror effect based on the context, culture, andbackground of the story.